Finite element analysis of pectus carinatum surgical correction via a minimally invasive approach - Neves, Sara C. (2015)
Pectus carinatum (PC) is a chest deformity caused by a disproportionate growth of the costal cartilages compared to the bony thoracic skeleton, pulling the sternum towards, which leads to its protrusion. There has been a growing interest on using the 'reversed Nuss' technique as a minimally invasive procedure for PC surgical correction. A corrective bar is introduced between the skin and the thoracic cage and positioned on top of the sternum highest protrusion area for continuous pressure. Then, it is fixed to the ribs and kept implanted for about 2-3 years. The purpose of this work was to (a) assess the stresses distribution on the thoracic cage that arise from the procedure, and (b) investigate the impact of different positioning of the corrective bar along the sternum. The higher stresses were generated on the 4th, 5th and 6th ribs backend, supporting the hypothesis of pectus deformities correction-induced scoliosis. The different bar positioning originated different stresses on the ribs' backend. The bar position that led to lower stresses generated on the ribs backend was the one that also led to the smallest sternum displacement. However, this may be preferred, as the risk of induced scoliosis is lowered.